ASPEK KELISANAN PADA LEGENDA KEâ LESAP KAJIAN SASTRA LISAN ALBERT B. LORD - , JIPHIE GILIA. I. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The existence of folklore in the society is a form of communication among the people which have many functions. Other than strengthens the bond of neighborhood among the people, folklore also functions as securing the old tradition of a certain society. Bangkalan is one of suburbs in Indonesia which have some legends which have its own local characteristics